(untitled) (Journal of Nepal Chemical Society, 2021)
A promising adsorbent, charred water hyacinth (CWH) for the removal of Ca(II) from the aqueous solution was explored by heat treatment of water hyacinth followed by chemical activation with acidified zinc chloride (ZnCl2). The adsorbent was characterized using scanning electron microscopy (SEM) and electron dispersive X-ray (EDX) spectroscopy. Batch adsorption techniques were conducted for Ca(II) adsorption to assess the adsorption isotherm, effect of pH, contact time, initial Ca(II) concentration, adsorbent doses, and adsorption kinetics. The SEM micrograph illustrates the rough and irregular surface morphology and EDX spectra confirm the successful adsorption of Ca(II) on the adsorbent surface. The equilibrium adsorption data better fitted to the Freundlich isotherm model having a maximum adsorption capacity (qmax) of 319.75 mg/g. The highest percentage of adsorption was found at pH 1.5. The adsorption of Ca(II) by CWH decreased at the higher metal concentration and lower adsorbent doses. The adsorption of Ca(II) ions onto CWH followed the pseudo-second-order kinetics model. . Overall, these results suggested that the as-prepared CWH can be used as an eco-friendly, economical and efficient alternative for the removal of Ca(II) from the aqueous solution.